Miniatures of Europe : Comparing Historical Master Narratives from Nineteenth-Century Belgium and Habsburg Central Europe - Tarafás, Imre (Historical Studies on Central Europe, 2025)
The study offers an unusual comparison: it sets out to compare historical master narratives from Belgium and Habsburg Central Europe. The first part justifies this approach by pointing out that Belgian and Austrian historians found themselves in a similar situation in the nineteenth century: their rivals considered their respective communities artificial constructs, as they lacked a national basis. Thus, Belgian and Austrian historians had the task of historically legitimizing their respective communities. These attempts are presented and evaluated, showing how the Belgian attempt was much more successful than its Austrian counterpart. The second part of the study examines nineteenth century Belgian and Hungarian representations of the reign of Joseph II, who not only ruled both territories but represented the same dilemma for historians in the nineteenth century in both countries: his modernizing measures greatly corresponded to nineteenth-century notions of progress; on the other hand, they also threatened cherished national institutions. The study shows the dividing lines between the various interpretations of Belgian and Hungarian historians treating this issue.